Biological Effects of Monoenergetic Carbon Ions and Their Associated Secondary Particles - Buglewicz, Dylan J.; Walsh, Kade D.; Hirakawa, Hirokazu; Kitamura, Hisashi; Fujimori, Akira; Kato, Takamitsu A. (Frontiers in Oncology, 2022)
DNA double strand breaks (DSBs) are the main actor behind carbon ion radiation therapy (CIRT) induced cell death. Nuclear interactions along the beam path between the primary carbon-ions and targets result in nuclear fragmentation of carbon-ions and recoiled particles. These secondary particles travel further distances past the Bragg peak to the tail region, leading to unwanted biological effects that may result in cytotoxicity in critical organs and secondary induced tumors following CIRT. Here, we confirmed that the density of the DSB distributions increases as the cell survival decreases at the Bragg peak and demonstrated that by visualizing DSBs, the various LET fragmentation-ions and recoiled particles produced differences in their biological effects in the post-Bragg peak tail regions. This suggests that the density of the DSBs within the high-LET track structures, rather than only their presence, is important for inducing cell death. These results are essential for CIRT treatment planning to limit the amount of healthy cell damage and reducing both the late effect and the secondary tumor associated